Comparison of Dimensional Accuracy of Digital Dental Models Produced from Scanned Impressions and Scanned Stone Casts. - Subeihi, Haitham. (2017)
Abstract: Introduction: Digital models of dental arches play a more and more important role in dentistry. A digital dental model can be generated by directly scanning intraoral structures, by scanning a conventional impression of oral structures or by scanning a stone cast poured from the conventional impression. An accurate digital scan model is a fundamental part for the fabrication of dental restorations. Aims: 1. To compare the dimensional accuracy of digital dental models produced by scanning of impressions versus scanning of stone casts. 2. To compare the dimensional accuracy of digital dental models produced by scanning of impressions made of three different materials (polyvinyl siloxane, polyether or vinyl polyether silicone). Methods and Materials: This laboratory study included taking addition silicone, polyether and vinyl polyether silicone impressions from an epoxy reference model that was created from an original typodont. Teeth number 28 and 30 on the typodont with a missing tooth number 29 were prepared for a metal-ceramic three-unit fixed dental prosthesis with tooth #29 being a pontic. After tooth preparation, an epoxy resin reference model was fabricated by duplicating the typodont quadrant that included the tooth preparations. From this reference model 12 polyvinyl siloxane impressions, 12 polyether impressions and 12 vinyl polyether silicone impressions were made. All 36 impressions were scanned before pouring them with dental stone. The 36 dental stone casts were, in turn, scanned to produce digital models. A reference digital model was made by scanning the reference model. Six groups of digital models were produced. Three groups were made by scanning of the impressions obtained with the three different materials, the other three groups involved the scanning of the dental casts that resulted from pouring the impressions made with the three different materials. Groups of digital models were compared using Root Mean Squares (RMS) in terms of their dimensional accuracy, which is defined as the absolute value of deviation in micrometers from the reference model. A two-way analysis of analysis of variance (ANOVA) was applied to calculate if the measurements for the six test groups were statistically significantly different from the original reference model as well as between test groups (p <.05). Tukey's HSD was also applied to characterize the differences. Results: The mean (± SD) RMS was 29.42 ± 5.80 microns for digital models produced from polyether impression scans, 27.58 ± 5.85 microns for digital models from PVS impressions scans, and 24.08 ± 4.89 microns for digital models produced from VPES impressions scans. 26.08 ± 6.58 microns for digital models produced by scanning stone casts poured from PE, 31.67 ± 9.95 microns for digital models produced by scanning stone casts poured from PVS and 22.58 ± 2.84 microns for digital models produced by scanning stone casts poured from VPES. In the Two-Way ANOVA, the p-value for the material factor was 0.004, reflecting a statistically significant difference between the accuracy of the three impression materials, with VPES showing the highest accuracy (mean RMS = 23.33 ± 3.99 microns) followed by PE (mean RMS = 27.75 ± 6.3 microns) and PVS (mean RMS = 29.63 ± 8.25 microns). For the technique factor, the p-value was 0.870 reflecting no statistically significant difference between the accuracy of the two techniques (impression scan and stone cast scan). The mean RMS values were 27.03 ± 5.82 microns and 26.78 ± 7.85 microns, respectively. In the post-hoc tests for the material factor, a significant difference was found between the accuracy of VPES and PVS (p-value = 0.004) with VPES having the higher accuracy (lower mean RMS). No significant difference was found between the accuracies of PE and PVS (p-value = 0.576), and between the accuracies of PE and VPES (p-value = 0.054). Conclusions: Within the limitations of this in vitro study, it can be concluded that: 1. There is no statistically significant difference in dimensional accuracy between digital models produced by scanning dental impressions and those produced by scanning stone casts. 2. Digital models produced from the scans of VPES impressions are dimensionally more accurate than those produced from PVS impressions scans. No significant difference in accuracy was observed between PE and PVS impression scans, or between PE and VPES impression scans.; Thesis (M.S.)--Tufts University, 2012.; Submitted to the School of Dental Medicine; Advisor: Hans-Peter Weber.; Committee: Hiroshi Hirayama, Roger Galburt, and Matthew Finkelman.; Keywords: Dentistry, and Materials Science.